Liposomes encapsulating cyclodextrin enclosed hydrophobic anti-cancer drugs: a novel drug delivery system for cancer.: Not required - Jani, Dr. Rupalben Kaushalkumar; Pandya, Mansi; Rathod, Hemali (Journal of Drug Delivery and Therapeutics, 2019)
In the current situation in the health care industry is to face many challenges to cure the cancer. The second highest death were noticed by the cancer in society. Therefore, the efficient treatment is required. There many treatmentsare available to cure the cancer but not found much efficient. The advance development in the hydrophobic drug in the form of water-soluble drug cyclodextrin complex in liposomes has been investigated. This new investigation in to the complex in liposomes play key role in combination of the cyclodextrin and liposomes in the one common system. Such system would potentially increase the drug to lipid mass ratio. In comparison to conventional treatment this ratio is high therefore it enlarges the range of insoluble drug amenable to encapsulation to include, allow targeting, of complexes to specific sites and reduce toxicity, for instance and membrane destabilizing agents. This extensive review explores the novel drug delivery for the cancer treatment. Keywords: Liposomes, cyclodextrin, anti-cancer, novel drug delivery system